LIM Homeobox 9 knockdown by morpholino does not affect zebrafish retinal development - Guo, Rui (Biol Open, 2021)
LIM homeobox 9 (Lhx9) is a member of the LIM homeodomain transcription factor family, which expresses and functions in various vertebrate tissues, such as the gonads and pineal gland. Previous studies on lhx9 in zebrafish have mainly focused on the brain. However, little is known about the expression pattern of lhx9 during embryogenesis. Here, we detected lhx9 expression in zebrafish embryos using whole-mount in situ hybridization and found lhx9 expressed in heart, pectoral fin, and retina during their development in zebrafish. We then detailed the expression of lhx9 in retinal development. To further investigate the function of Lhx9 in retinogenesis, we performed morpholino (MO) knockdown experiments and found that upon lhx9 knockdown by MO, larvae presented normal eye development, retinal neural development, differentiation, proliferation, apoptosis, and responses to light stimulus. We not only elaborated the expression pattern of lhx9 in zebrafish embryogenesis, but we also demonstrated that lhx9 knockdown by morpholino does not affect the zebrafish retinal development, and our study provides data for further understanding of the role of Lhx9 in zebrafish retinal development.